Socio-Economic Determinants of Individual Muslim Zakat Payment Behavior in Indonesia - Hapid Durohman; Fajar Adrian Sutisna; Muhammad Yuka Anugrah (Journal of Islamic Economics and Finance Studies, 2023)
Zakat is one of the pillars of Islam and holds significant potential in Indonesia. However, the amount of zakat collected remains far below its potential. This disparity arises because many Muslims neglect zakat payment and perceive it as less important. Therefore, it is crucial to understand the socio-economic behaviors and factors influencing individual decisions to pay zakat. This research aims to investigate the determinants of socio-economic factors on individual zakat behavior. The data utilized is sourced from the Indonesian Family Life Survey (IFLS) conducted in 2014, focusing on individuals aged 15 and above. The study employs probit regression methodology to examine individual decisions regarding zakat payments, utilizing STATA 17 for analysis. The research findings statistically indicate that individuals with higher socio-economic status have a greater likelihood of paying zakat. This is evident from socio-economic variables, including gender, household size, age, home ownership, loans, years of schooling, income, religiosity, and occupation, all significantly influencing individual decisions to contribute to zakat. However, variables such as place of residence and marital status do not significantly affect individuals' decisions to pay zakat. Therefore, socio-economic factors play a crucial role in formulating strategies to enhance zakat fund collection. Zakat institutions can refer to socio-economic research to determine their strategies for maximizing the significant zakat potential in Indonesia. For instance, by targeting income levels, zakat institutions can develop awareness programs for individuals with higher incomes, accelerating zakat fund collection in alignment with its substantial potential.   Zakat adalah salah satu pilar Islam dan memiliki potensi besar di Indonesia. Namun, jumlah zakat yang terkumpul masih jauh di bawah potensinya. Ketidaksetaraan ini muncul karena banyak Muslim yang mengabaikan pembayaran zakat dan menganggapnya kurang penting. Oleh karena itu, sangat penting untuk memahami perilaku sosial-ekonomi dan faktor-faktor yang memengaruhi keputusan individu untuk membayar zakat. Penelitian ini bertujuan untuk menyelidiki faktor-faktor sosial-ekonomi yang memengaruhi perilaku zakat individu. Data yang digunakan berasal dari Indonesian Family Life Survey (IFLS) yang dilakukan pada tahun 2014, dengan fokus pada individu yang berusia 15 tahun ke atas. Studi ini menggunakan metodologi regresi probit untuk menguji keputusan individu tentang pembayaran zakat, dengan menggunakan STATA 17 untuk analisis. Temuan penelitian secara statistik menunjukkan bahwa individu dengan status sosial-ekonomi yang lebih tinggi memiliki kemungkinan yang lebih besar untuk membayar zakat. Hal ini terlihat dari variabel sosial-ekonomi, termasuk jenis kelamin, ukuran rumah tangga, usia, kepemilikan rumah, pinjaman, tahun-tahun sekolah, pendapatan, religiusitas, dan pekerjaan, yang semuanya secara signifikan memengaruhi keputusan individu untuk berkontribusi pada zakat. Namun, variabel seperti tempat tinggal dan status pernikahan tidak secara signifikan memengaruhi keputusan individu untuk membayar zakat. Oleh karena itu, faktor-faktor sosial-ekonomi memainkan peran penting dalam merumuskan strategi untuk meningkatkan pengumpulan dana zakat. Institusi zakat dapat merujuk pada penelitian sosial-ekonomi untuk menentukan strategi mereka dalam memaksimalkan potensi zakat yang signifikan di Indonesia. Sebagai contoh, dengan melihat tingkat pendapatan, institusi zakat dapat mengembangkan program-program kesadaran untuk individu dengan pendapatan lebih tinggi, mempercepat pengumpulan dana zakat sesuai dengan potensi yang substansial.